2022
DOI: 10.2196/40831
|View full text |Cite
|
Sign up to set email alerts
|

An Accessible Clinical Decision Support System to Curtail Anesthetic Greenhouse Gases in a Large Health Network: Implementation Study

Abstract: Background Inhaled anesthetics in the operating room are potent greenhouse gases and are a key contributor to carbon emissions from health care facilities. Real-time clinical decision support (CDS) systems lower anesthetic gas waste by prompting anesthesia professionals to reduce fresh gas flow (FGF) when a set threshold is exceeded. However, previous CDS systems have relied on proprietary or highly customized anesthesia information management systems, significantly reducing other institutions’ acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Wu et al conducted an implementation effectiveness trial for examining the clinical impact of patient-oriented and provider-facing CDS report for health risk assessment [7]. Notably, one study demonstrated the scalability and transferability of a CDS system to reduce anesthetic gas waste [8], innovatively linking informatics solutions to environmental impact.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al conducted an implementation effectiveness trial for examining the clinical impact of patient-oriented and provider-facing CDS report for health risk assessment [7]. Notably, one study demonstrated the scalability and transferability of a CDS system to reduce anesthetic gas waste [8], innovatively linking informatics solutions to environmental impact.…”
Section: Resultsmentioning
confidence: 99%
“…Structural aspects include the type of CDS and clinical setting where the CDS was deployed or studied. Six studies included domain-specific systems such as an electronic alert to notify prescribers about inappropriate red blood cell and platelet transfusion [6]; a patient-specific CDS report for disease prevention and surveillance in the primary care setting [7]; a non-interruptive alert in anesthesia to reduce fresh gas flow when a predefined threshold was exceeded [8]; a real-time text message alert when antimicrobial therapy was inappropriate (i.e., an antimicrobial agent-pathogen mismatch with a positive blood culture result) [9]; a guideline-based CDS for maternal health [10]; and a microRNA-based thyroid molecular…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…For example, individual hospital systems, such as University of California–San Francisco (UCSF) hospitals and Yale University Hospital, are utilizing electronic health records to change the type of and reduce the flow rate of anesthetic gases. 33 , 34 On the national level, Practice GreenHealth (a nonprofit collaborative focused on developing environmentally conscious solutions for healthcare) facilitates multiorganizational collaborations in running pilots and scaling efforts. 38 Additionally, many case examples also document clear financial incentives and outcomes (such as the cost savings cited by CommonSpirit and Kaiser).…”
Section: Key Themes To Implement Decarbonization Practicesmentioning
confidence: 99%
“…Artificial intelligence and machine learning, which seemed quixotic years ago, have made an unexpectedly large leap with several potential applications, such as reducing medication errors, perioperative risk assessment, early detection of clinical deterioration, predicting postoperative morbidity and mortality, streamlining workflows, creating personalized care pathways, real-time image analysis, providing clinical decision support, analysis of structured and unstructured data in electronic health records, or understanding health disparities [10][11][12]. Experts in perioperative medicine are investigating a broad range of topics-from sustainability and the carbon footprint of surgeries to taking a deeper dive into precision medicine using omics and biomarkers [13]. Some of these discoveries and research will reduce inequities and improve surgical safety on a global scale while others may improve outcomes and care delivery locally, both of which are important.…”
mentioning
confidence: 99%